DESIGNING AND OPTIMIZATION OF NAPROXEN SODIUM DEFORMABLE VESICULAR SYSTEMS THROUGH FACTORIAL DESIGN: BOX BEHENKEN MODEL - GUPTA, NAVEEN; JAIN, SHAILESH (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of this investigation was to develop and statistically optimize deformable vesicles such as transfersomes and transethosomes of Naproxen sodium by employing 33factorial designs through software Design expert version 12 (Box–Behnken design) for dermal delivery. Methods: The levels of the drug, phosphatidylcholine, and span 80 (independent variables) were varied to study the influence on vesicle size and % entrapment efficiency (dependent variables) of transfersomes and for transethosomes, the levels of phosphatidylcholine, ethanol, and span 80 were selected as independent variables Second-order quadratic polynomial equation, 2D and 3D contour plots represented the relationship between variables and desired response. The optimization process was carried out using desirability plots and point prediction techniques. Results: Results of the present study demonstrated that optimized transfersomes and transethosomes showed vesicle sizes of 114.91 nm and 102.91 nm respectively, while entrapment efficiency of 80.11 % and 86.97%, respectively. Both formulations showed high zeta potential values indicating the stability of the optimized formulation. ANOVA statistical results showed a significant difference (P<0.05). Conclusion: The results indicated that the independent variable plays a crucial role in optimizing a formulation that can be used for further research studies. Present preliminary study data provided strong evidence that the optimized deformable vesicular formulations through box Behnken factorial design can be a potentially useful drug carrier for naproxen sodium dermal delivery with minimum vesicle size and efficient entrapment efficiency.